A Farewell to Arms in the 21st Century: The Case of the Moro Islamic Liberation Front - Yunus Çolak (Siyasal: Journal of Political Sciences)
This study examined the policy change of the Moro Islamic Liberation Front (MILF) during the 21st century and offered an explanatory typology for changes in the secessionist movements’ aims and/or means through which they pursue their aims. It is possible to find studies that analyze the disarmament of the MILF and renouncing its goal for independence as a policy change in the 21st Century with reference to the involvement of international third parties, the determination of the leaders of the parties for peace, and the military balance in the field. Although all these perspectives are very helpful to understand MILF’s policy change, this study argues that the above-mentioned change has occurred as a result of the change in MILF leadership’s perceptions of the international conjuncture and great power politics in the 21st century. In addition, C. F. Hermann’s typology of changes regarding states’ foreign policies adapted to secessionist movements with a few additions and exclusions to analyze MILF’s policy changes during the 21st Century. Thus, according to this typology, during the 21st century, a “problem/goal change” has occurred in the MILF policy, which has renounced the goal for independence, settling for autonomy. The source of this “problem/goal change” is categorized as a “leader-driven change” under the influence of an “external shock.”